The need for deep rest: Six stories of critical grief pedagogy - Collins, Kimberlee; Chelsea Temple; pierson, sarah; Desroches, Janice; Bagga, Guneet; Crosby, Morgan (Journal of Praxis in Higher Education, 2025)
This paper reimagines the four tenants of critical grief pedagogy (CGP) through entwined narratives of and teachings on grief by introducing a fifth, essential tenant for engaging with CGP: the deep need for rest. Storied around their 2022 delivery of a digital Death Café for graduate students in a master’s-level disability justice course, Collins and Jones reframe CGP in the classroom through lenses of disability justice and methodologies of collective narrative. In collaboration with four student participants from the Death Café, this article responds to our interdependent grief experiences of the COVID-19 pandemic, climate change, madness, anticipatory grief, and the relationalities of these modes of grief. This paper is a gathering of those conversations and our collective writing. Through these narrative experiences, we engage in a mode of collaborative exploration, composition, and de-composition. We explore what it means to take teaching and learning as a ‘grief-facing’ praxis that changes how we engage with embodiment in higher education. In what follows, our entwined responses to the Death Café remind us that grief is ubiquitous and expansive in academic spaces, and that rest is essential and political.